Genetic structure and evolution of Alpine polyploid complexes: Ranunculus kuepferi (Ranunculaceae) as a case study - Burnier, Julien; Buerki, Sven; Arrigo, Nils; Küpfer, Philippe; Alvarez, Nadir (My University, 2009)
The alpine white-flowered buttercup, Ranunculus kuepferi Greuter & Burdet, is a polyploid complex with diploids endemic to the southwestern Alps and polyploids – which have been previously described as apomictic – widespread throughout European mountains. Due to the polymorphic status of both its ploidy level and its reproductive mode, R. kuepferi represents a key species for understanding the evolution of polyploid lineages in alpine habitats. To disentangle the phylogeography of this polyploid taxon, we used cpDNA sequences and AFLP (amplified fragment length polymorphism) markers in 33 populations of R. kuepferi representative of its ploidy level and distribution area. Polyploid individuals were shown to be the result of at least two polyploidization events that may have taken place in the southwestern Alps. From this region, one single main migration of tetraploids colonized the entire Alpine range, the Apennines and Corsica. Genetic recombination among tetraploids was also observed, revealing the facultative nature of the apomictic reproductive mode in R. kuepferi polyploids. Our study shows the contrasting role played by diploid lineages mostly restricted to persistent refugia and by tetraploids, whose dispersal abilities have permitted their range extension all over the previously glaciated Alpine area and throughout neighbouring mountain massifs.
Keywords: AFLP; apomixis; cpDNA network; phylogeography; polyploidy; Ranunculaceae